Growth Mindset and Arabic Speaking Skills: A Systematic Literature Review Using PRISMA 2020 - Arsyad, Hairuddin; Abdurrahman, Maman; Sopian, Asep (ELITE JOURNAL, 2025)
This study aims to explore the role of a growth mindset in enhancing Arabic speaking skills, with implications for developing more effective learning strategies. Although increasing attention has been given to affective factors in language learning, the literature specifically linking growth mindset to Arabic speaking skills remains very limited. This research employs a Systematic Literature Review approach following the PRISMA 2020 guidelines. Articles were retrieved from Scopus, Google Scholar, and Sage databases within the 2018-2025 timeframe. Out of 642 identified publications, only 27 articles met the inclusion criteria and were further analyzed. The findings indicate that a growth mindset positively contributes to improving students’ motivation, self-confidence, and perseverance in speaking skills. In addition, this review reveals a gap in the literature, as most studies still focus on English and Mandarin, while Arabic has not been adequately explored. This study is significant as it provides both theoretical and empirical foundations for developing Arabic language learning strategies based on a growth mindset, while also opening opportunities for further research to test direct interventions in formal educational contexts in developing countries, including Indonesia. Keywords: Growth Mindset, Arabic Language, Speaking Skills, Foreign Language Learning